Effect of Isometric Handgrip Exercise on Sleep Quality of Hypertension Patients in the Elderly - Lucya, Vita; Pratiwi, Gilang Dwi; Anggie, Novita (STIKep PPNI Jawa Barat, 2024)
Aims: The study aimed to knowing the effect of isometric handgrip exercise on the quality of sleep of hypertension patients in the elderly. Methods: The study was Quasi Experiment research with one group pretest-posttest design. The study population was purposive sampling and obtained a total of 30 respondents. This research was conducted at the Sukawarna Health Center Work Area, Bandung City. The instrument used was PSQI (Pittsburgh Sleep Quality Index). Results: There was an effect ofisometric handgrip exercise on the quality of sleep of hypertension patients in the elderly (p-value = 0,000). Conclusion: Isometric handgrip exercise is a non-pharmacological therapy that can be used to improve quality of sleep of hypertension patients in the elderly.